Assessment of palliative patients with chemoresistance pulmonary tuberculosis life quality in the conditions of specialized hospital at the corrective labour colony - Raznatovska, O. M.; Khudyakov, G. V.; Разнатовська, Олена Миколаївна; Худяков, Г. В.; Разнатовская, Е. Н.; Худяков, Г. В. (Zaporizhzhya state medical university, 2017)
Objective – to evaluate the quality of life of palliative patients with drug-resistant pulmonary tuberculosis at a specialized hospital penal colony in terms of the questionnaire of the MOS SF-36 and justify the appropriateness of its application for a differentiated approach in dependence of physical or mentally health components oppression, monitoring their health status. Materials and Methods. Quality of life assessment was performed in 95 patients with drug-resistant pulmonary tuberculosis who were treated in a specialized tuberculosis hospital at the penal colony. 53 patients of them were on palliative treatment and included into main observation group and comparison group consisted of 42 patients who received antimycobacterial chemotherapy in the maintenance phase of treatment. To determine the norms of quality studied indicators in our region, we have formed a control group consisted of 40 healthy volunteers. For quality of life assessment the questionnaire of the MOS SF-36 was used. Results. Increase the intensity of pain in palliative patients with drug-resistant pulmonary tuberculosis contributes physical functioning limitation. Acute emotional instability (depression, anxiety and negative emotions) with limited social activity causes low self-esteem of mental state. Such changes ultimately result in inhibition of the viability and general health deterioration. For these patients particular attention should be paid to such scale of life quality assessment as PF, VT and MH as they were significantly lower compared with those drug-resistant pulmonary tuberculosis patients with antimycobacterial chemotherapy in maintenance phase of treatment. Conclusions. Drug-resistant tuberculosis in patients who are in palliative care leads to a drastic reduction of all quality of life parameters. Using the questionnaire of the MOS SF-36 for quality of life in palliative patients with drug-resistant pulmonary tuberculosis assessment is reasonable for a differentiated approach in dependence of physical or mentally health components oppression, health monitoring of these patients. Мета роботи – оцінити якість життя паліативних хворих на хіміорезистентний туберкульоз легень в умовах спеціалізованої лікарні при виправній колонії за показниками опитувальника MOS SF-36 та обґрунтувати доцільність його застосування для диференційованого підходу надання допомоги залежно від пригнічення фізичного чи психічного компонентів здо¬ров’я, моніторингу стану їхнього здоров’я. Матеріали та методи. Оцінювання якості життя здійснили у 95 хворих на хіміорезистентний туберкульоз легень, які перебували на лікуванні в умовах спеціалізованої лікарні при виправній колонії. З них в основну групу ввійшли 53 осо¬би, які перебували на паліативному лікуванні. Група порівняння – 42 пацієнти, які одержували антимікобактеріальну хіміотерапію в підтримувальну фазу лікування. Для визначення норми досліджуваних показників якості в нашому регіоні створена контрольна група, до якої ввійшли 40 здорових добровольців. Для оцінювання якості життя використовували опитувальник MOS SF-36. Результати. У паліативних хворих на хіміорезистентний туберкульоз легень наростання інтенсивності болю сприяє обмеженню фізичного функціонування. Різка емоційна нестабільність (депресії, тривоги, негативні емоції) з обмеженням соціальної активності сприяють зниженню самооцінки психічного стану. Такі зміни в підсумку призводять до пригнічення життєздатності та погіршення загального стану здоров’я. Особливої уваги заслуговують у цих хворих такі шкали якості життя, як PF, VT і МН, оскільки вони були вірогідно нижчими порівняно з хворими на хіміорезистентний туберкульоз легень, які отримували антимікобактеріальну хіміотерапію в підтримувальну фазу лікування. Висновки. У паліативних хворих хіміорезистентний туберкульоз призводить до різкого зниження всіх параметрів якості життя. Використання опитувальника MOS SF-36 для оцінювання якості життя в паліативних хворих на хіміорезистентний туберкульоз легень є доцільним для диференційованого підходу надання допомоги залежно від пригнічення фізичного чи психічного компонентів здоров’я, моніторингу стану здоров’я цих пацієнтів. Цель работы – оценить качество жизни паллиативных больных химиорезистентным туберкулёзом лёгких в усло¬виях специализированной больницы исправительной колонии по показателям опросника MOS SF-36 и обосновать целесообразность его применения для дифференцированного подхода оказания помощи в зависимости от угнетения физического или психического компонентов здоровья, мониторинга состояния их здоровья. Материалы и методы. Оценку качества жизни провели у 95 больных химиорезистентным туберкулёзом лёгких, которые находились на лечении в условиях специализированной больницы при исправительной колонии. Из них в основную группу вошли 53 больных, которые находились на паллиативном лечении, и в группу сравнения – 42 больных, кото¬рые получали антимикобактериальную химиотерапию в поддерживающей фазе лечения. Для определения нормы исследуемых показателей качества в нашем регионе была создана контрольная группа, в которую вошли 40 здоровых добровольцев. Для оценки качества жизни использовали опросник MOS SF-36. Результаты. У паллиативных больных химиорезистентным туберкулёзом лёгких нарастание интенсивности боли спо¬собствует ограничению физического функционирования. Резкая эмоциональная нестабильность (депрессия, тревога и негативные эмоции) с ограничением социальной активности способствуют снижению самооценки психического состояния. Такие изменения в итоге приводят к угнетению жизнеспособности и ухудшению общего состояния здоровья. Особого внимания заслуживают у этих больных такие шкалы качества жизни, как PF, VT и МН, поскольку они были достоверно ниже по сравнению с больными химиорезистентным туберкулёзом лёгких, получавшими антимикобактериальную химиотерапию в поддерживающую фазу лечения. Выводы. У паллиативных больных химиорезистентный туберкулёз ведёт к резкому снижению всех параметров качества жизни. Использование опросника MOS SF-36 для оценки качества жизни у паллиативных больных химиорезистентным туберкулёзом лёгких целесообразно для дифференцированного подхода оказания помощи в зависимости от угнетения физического или психического компонентов здоровья, мониторинга состояния здоровья этих пациентов.
Оцінювання якості життя паліативних хворих на хіміорезистентний туберкульоз легень в умовах спеціалізованої лікарні при виправній колонії
Оценка качества жизни паллиативных больных химиорезистентным туберкулёзом лёгких в условиях специализированной больницы при исправительной колонии
Keywords: drug-resistant tuberculosis; palliative care; assessment of quality of life; questionnaire of the MOS SF-36; хіміорезистентний туберкульоз легень; паліативне лікування; якість життя; опитувальник MOS SF-36; химиорезистентный туберкулёз лёгких; паллиативное лечение; качество жизни; опросник MOS SF-36